Antecedent of consumer purchase decisions on pegipegi.com - Suardhika, I Nengah; Rihayana, I Gede; Wirangjani, Ida Ayu Putu (International Journal of Communication and Society, 2024)
Technology advances have created a map of competition in the Online Travel Agent (OTA) service provider industry in Indonesia. Pegipegi.com as an online service provider is one of the competitors whose sales fluctuate from year to year. In this study used 97 respondents with data analysis using Smart PLS 3.0. examination the research conducted revealed that brand trust had a significant positive impact on purchasing decisions, then experiential marketing also had a significant positive impact on purchasing decisions and so does e-promotion variables which had a significant positive effect on purchases decisions.